WITHAFERIN A INDUCES APOPTOSIS IN RAT C6 GLIOMA CELLS THROUGH REGULATING NF- ΚB NUCLEAR TRANSLOCATION AND ACTIVATION OF CASPASE CASCADE - Hou, Wei-chen; Miao, Xiao-hui; Ma, Lian-jun; Bai, Xiao-xue; Liu, Qun; Song, Lei (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The demand for the chemopreventive drug from the plant source is increasing in recent times, owing toits various biological activities without any adverse effect. The intention of this current study was to examine the antigliomaeffect of Withaferin A (WFA) on C6 glioma cell line model.Materials and Methods: C6 glioma cells were administrated with different concentration of WFA (50, 100, 200 and500 μg/mL) and DMSO (control) group to examine its anti-proliferative, anti-inflammatory and pro-apoptotic activities.Results: Treatment with WFA showed a significant decline in the glioma cell count in a dose-dependent manner andthus proving its anti-proliferative effect. Similarly, inflammatory markers were also substantially lowered upontreatment with different concentration of WFA. However, DNA fragmentation and apoptotic markers like Caspase-3and 9 were concomitantly enhanced after co-cultured with different concentration of WFA and thus exhibiting itscytotoxicity efficacy. Furthermore, the protein expression of Bcl2 and Bax were markedly downregulated andupregulated respectively; upon treatment with WFA on C6 glioma cells.Conclusion: The outcome of this study evidently demonstrates that C6 glioma cells co-cultured with increasedconcentration of WFA, showed an anti-proliferative, anti-inflammatory and pro-apoptotic effect in a dose-dependentfashion.